2000
DOI: 10.1892/0891-6640(2000)014<0165:eolpto>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Phenobarbital Treatment on the Liver in Dogs

Abstract: Long-term administration of phenobarbital has been reported to cause hepatic injury in dogs. Phenobarbital induces hepatic enzymes, and it may be difficult to distinguish the effect of enzyme induction on serum liver enzyme activities from actual hepatic damage. The hepatotoxicity of phenobarbital and the impact of enzyme induction on serum liver enzyme activity were investigated prospectively in 12 normal dogs. Phenobarbital was administered for 29 weeks at 5 mg per kilogram of body weight (range, 4.8-6.6 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
0
5
0
2
Order By: Relevance
“…Similarly the dog has also been reported to be less sensitive to the barbiturate than are rodents (McKillop, 1985;Muller et al, 2000) and in general both the nonhuman primate and the dog have been reported to be less responsive to the induction of enzymes by so-called classic inducers of rodent hepatic enzymes. Figure 10 gives some data from the paper by Amacher et al (2001) on the hepatic response of the dog liver to a number of rodent hepatic enzyme inducing chemicals.…”
Section: Drug-induced Nonneoplastic Hepatic Changesmentioning
confidence: 99%
“…Similarly the dog has also been reported to be less sensitive to the barbiturate than are rodents (McKillop, 1985;Muller et al, 2000) and in general both the nonhuman primate and the dog have been reported to be less responsive to the induction of enzymes by so-called classic inducers of rodent hepatic enzymes. Figure 10 gives some data from the paper by Amacher et al (2001) on the hepatic response of the dog liver to a number of rodent hepatic enzyme inducing chemicals.…”
Section: Drug-induced Nonneoplastic Hepatic Changesmentioning
confidence: 99%
“…Although most dogs suffering from idiopathic epilepsy (IE) respond well to phenobarbital (PB) monotherapy, 20 to 30% respond inadequately even to a combination of conventional antiepileptic drugs (AED) including PB and potassium bromide (KBr) (Farnbach 1984, Schwartz-Porsche et al 1985, Podell & Fenner 1993, Trepanier et al 1998. Increasing the dosages of PB and KBr in order to decrease the seizure frequency may lead to various adverse effects such as polydipsia, polyuria, polyphagia, sedation, ataxia, weight gain and liver toxicity (Schwartz-Porsche et al 1985, Podell & Fenner 1993, Müller et al 2000. Since poor seizure control and unacceptable side effects decrease the quality of life of dogs with IE and recurrent epileptic seizures may predispose to premature death or euthanasia (Chang et al 2006, Berendt et al 2007, novel effective and safe AEDs are needed to treat these pharmacoresistant patients.…”
Section: Introductionmentioning
confidence: 99%
“…In most dogs, these side effects usually are tolerated after 2 to 4 weeks of therapy [10]. No actual hepatocellular damage during PB treatment has been confirmed; however, PB administration can contribute to the induction of serum liver enzyme activities in dogs [2,8]. In addition, PB has infrequently been associated with hematologic adverse drug events (ADEs) in dogs, including reversible neutropenia, thrombocytopenia, and anemia [5,6].…”
mentioning
confidence: 99%